Three-phase hybrid active power filter: an overview - Binh, Le Quang; Thuyen, Chau Minh (Institute of Advanced Engineering and Science, 2025)
Hybrid active power filter (HAPF) is considered an effective solution for filtering harmonics and compensating reactive power in power systems. It is a combination of passive power filters and an active power filter to form many different structures depending on the system voltage and load characteristics. This paper aims to introduce an overall picture of the results of research on three-phase HAPF systems, such as: HAPF models, advantages, disadvantages, and scope of application of each model; methods for determining parameters of passive power filters; structure, response time, resonance, power loss and cost of types of output filters; inverter structure and commonly used pulse width modulation methods in HAPF; control strategies and used controllers are also listed and compared; the DC Link voltage stabilization is also summarized and analyzed. Finally, the existing problems and the development trends of HAPF.